Factors Associated with Prolonged Mechanical Ventilation and 30-Day Mortality in Intubated COVID-19 Patients with Invasive Fungal Infections: A Retrospective Observational Study - Hung Manh Than; Thang Van Dao; Truong Van Cao; Tuyen Van Duong; Thach Ngoc Pham; Cap Trung Nguyen; Phu Dinh Vu; Nam Van Le; Binh Nhu Do; Phuong Viet Nguyen; Ha Nhi Vu; Duong Minh Vu (Tropical Medicine and Infectious Disease)
COVID-19-associated invasive fungal infections (CAIFIs) contribute to increased mortality and morbidity rates. This study explores the epidemiology, laboratory parameters, radiological characteristics, treatments, and 30-day mortality risks of CAIFI in critically ill intubated patients while also evaluating factors associated with prolonged mechanical ventilation (PMV) in this population. Adults admitted to a tertiary hospital from 1 April 2021 to 31 March 2022 who were diagnosed with severe COVID-19, required invasive mechanical ventilation, and developed invasive fungal infection (IFI) during hospitalization were analyzed in this retrospective cohort study. Among 150 patients, 65 (43.3%) required PMV, with an in-hospital mortality rate of 64%. Candida albicans (47%) and Aspergillus fumigatus (27%) were the most prevalent pathogens. Multivariate analysis revealed that COVID-19 vaccination (adjusted odds ratio, aOR = 0.155, 95% confidence interval, 95% CI = 0.029–0.835, p = 0.030) and higher serum protein levels (aOR = 0.900, 95% CI = 0.819–0.989, p = 0.028) were significantly associated with a reduced risk of PMV. Meanwhile, elevated glucose levels (hazard ratio, HR = 1.047, 95% CI = 1.003–1.093, p = 0.036) and an increased neutrophil-to-lymphocyte ratio (HR = 1.024, 95% CI = 1.009–1.039, p = 0.002) were correlated with a greater 30-day mortality risk. Tracheostomy emerged as a protective factor, significantly reducing the risk of 30-day mortality (HR = 0.273, 95% CI = 0.127–0.589, p = 0.001). In this single-center study, patients with CAIFI exhibit a high mortality rate. Clinicians should maintain vigilance for IFI in critically ill COVID-19 patients with mechanical ventilation.